An analysis of causative factors in closed criminal medical malpractice cases of the Taiwan Supreme Court: 2000–2014. (November 2016) - Wu, Kuan-Han; Cheng, Shih-Yu; Yen, Yung-Lin; Wu, Chien-Hung; Tsai, Ming-Ta; Cheng, Fu-Jen
Highlights: Totally 75% of criminal malpractice cases proved innocent after mean 7.6-year judicial process. All guilty clinicians avoided imprisonment via probation or replacement with forfeit. Emergency medicine was the single most risky specialty in criminal prosecution. About quarter of rulings were commuted, which might related to controversial appraisal result. Abstract: Most medical malpractice in Taiwan leads to criminal prosecution. This study examined the epidemiologic factors and clinical errors that led to medical malpractice convictions in Taiwanese criminal prosecutions. A retrospective, 15-year population-based review of criminal Supreme Court judgments pertaining to medical malpractice against physicians and nurses was conducted. Eighty-four cases were reviewed, yielding data that included the number and specialty involved, accused hospitals, the diagnosis, the time interval between incidents to closure, result of adjudication, the origin of cases (private vs. public prosecution), the result of medical appraisal, and the primary error. Overall, the cases averaged 7.6 years to achieve final adjudication. Seventy-five percent were settled in favor of the clinician; twenty-three physicians and three nurses were found guilty, but all of these avoided imprisonment via probation or replacement with forfeit. The single most risky specialty was emergency medicine (22.6% of the cases), with 36.8% of those resulting in guilty verdicts. The most common diagnosis groups were infectious diseases (23.8%), intracranial hemorrhages (10.7%), and acute coronary syndrome (9.5%). Public prosecutions had a 41.2% conviction rate; no guilty verdicts resulted from private prosecution. Nineteen (22.6%) cases were commuted, and 73.7% of those had a controversial appraisal result. The characteristics of criminal malpractice prosecution in Taiwan that could be improved to relieve the stress of frivolous lawsuits on the judicial process include lengthy jurisdiction process; low public-prosecution conviction rate; frequent commuted jurisdiction related to a controversial appraisal; and zero imprisonment rate for clinicians.